Lessons in Chemistry - Garmus, Bonnie (New York : Doubleday, 2022)
"Set in 1960s California, this ... debut is the ... story of a female scientist whose career is constantly derailed by the idea that a woman's place is in the home, only to find herself starring as the host of America's most beloved TV cooking show"--
Keywords: Women scientists -- Fiction; Single mothers -- Fiction; Television cooking shows -- Fiction; Fiction; Adult Fiction